Repeat sales index for residential real estate in Krakow - Jaroslaw Czerski; Michal Gluszak; Robert Zygmunt (Institute of Economic Research (IER), 2017)
Research background: There are several methods to construct a price index for infrequently traded real estate assets (mainly residential, but also office and land). The main concern to construct a valid and unbiased price index is to address the problem of heterogeneity of real estate, or put differently to control for both observable and unobservable quality attributes. Most frequently used is probably hedonic regression methodology (classic, but recently also spatial and quantile regression). An alternative approach to control for unobservable differences in assets' quality is provided by repeat sales methodology, where price changes are tracked based on differences in prices of given asset sold twice (or multiple times) within the study period. The later approach is applied in famous S&P CoreLogic Case-Shiller house price indices. Purpose of the article: The goal of the paper is to assess the applicability of repeat sales methodology for a major housing market in Poland. Previous studies used hedonic methodology or mix adjustment techniques and applied for major metropolitan areas. Most known example is a set of quarterly house price indices constructed by NBP - especially for primary and secondary market. The repeat sales methodology has not been adopted with significant success to date - mainly because of concern regarding relative infrequency of transactions on housing market in most metropolitan areas (thus potentially small sample of repeated sales). Methodology/methods: The study uses data on repeat sales of residential transactions in Krakow from 2003 to 2015. We apply different specifications of repeat sales index construction and compare respective values to hedonic price index for Krakow estimated by NBP. Findings: Findings suggest that repeat sales house sales indices can be used to track price dynamics for major metropolitan areas in Poland. The study suggests problems that need to be addresses in order to get unbiased results - mainly data collection mechanism and estimation procedure.
Keywords: C18; C43; R31; 330; repeat sales index; Poland; housing market; house price; real estate